Methodology for developing teaching activities and materials for use in fluid mechanics courses in undergraduate engineering programs - Pedro Javier Gamez-Montero; Gustavo Raush; Lluis Domenech; Robert Castilla; Mercedes Garcia-Vilchez; Hipolit Moreno; Albert Carbo (OmniaScience, 2015)
"Mechanics" and "Fluids" are familiar concepts for any newly-registered engineering student. However, when combined into the term "Fluid Mechanics", students are thrust into the great unknown. The present article demonstrates the process of adaptation employed by the Fluid Mechanics course in the undergraduate engineering program, along with the teaching methodology, teaching materials and results obtained, evaluating the final objective in terms of student satsfaction and level of learning.